NOTCH1 and FBXW7 mutations favor better outcome in pediatric South Indian T-cell acute lymphoblastic leukemia - Natarajan, Valliyammai; Bandapalli, Obul Reddy (Journal of pediatric hematology - oncology, 2015)
The NOTCH1 signaling pathway is essential for hematopoiesis and a critical regulatory step for T-cell proliferation and maturation. The E3 ubiquitin ligase FBXW7 controls NOTCH1 protein stability. Mutations in NOTCH1/FBXW7 activate NOTCH signaling and are of prognostic significance in patients with T-cell acute lymphoblastic leukemia (T-ALL). In this study we analyzed NOTCH1 and FBXW7 mutations in 50 South Indian T-ALL patients treated by a modified ALL BFM 95 regimen. The hot spot exons (HD-N, HD-C, TAD, and PEST) of NOTCH1 and exons 9 of the 10 of FBXW7 were polymerase chain reaction amplified and sequenced. In total, 20 of the 50 (40%) T-ALL patients revealed heterozygous mutations in the NOTCH1 domains, and a predominance of missense mutations in HD-N (70%) and PEST (15%) domains. FBXW7 mutations were detected in 5 of the 50 (10%) T-ALL patients. T-ALL patients with NOTCH1/FBXW7 mutations expressed higher protein level of NOTCH1 compared with patients without NOTCH1/FBXW7 mutations. Six of the mutations detected in NOTCH1 were not reported previously. When tested in a Dual Luciferase Renilla reporter assay some of these conferred increased NOTCH activity, suggesting that these are activating mutations. Importantly, 13 of the 20 (65%) NOTCH1/FBXW7-mutated T-ALL patients showed a good prednisone response (P=0.01) and a better clinical outcome compared with NOTCH1/FBXW7 nonmutated patients (P=0.03). These data suggest that NOTCH1/FBXW7 mutations are present in T-ALL patients from Southern India and may be useful biomarkers to predict prognosis in T-ALL.
Gesehen am 14.08.2020